2023
DOI: 10.1007/s00429-023-02618-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ventral tegmental area projections to the nucleus accumbens shell increases premature responding in the five-choice serial reaction time task in rats

Abstract: Exaggerated impulsivity and attentional impairments are hallmarks of certain disorders of behavioural control such as attention-deficit/hyperactivity disorder (ADHD), schizophrenia and addiction. Pharmacological studies have implicated elevated dopamine (DA) levels in the nucleus accumbens shell (NAcbS) in impulsive actions. The NAcbS receives its DA input from the ventral tegmental area (VTA), and we have previously shown that optogenetic activation of VTA-NAcbS projections impaired impulse control and attent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In addition, considering the functional antagonism in the control over waiting impulsivity between the NAc Shell and the NAc Core, the latter promoting impulsive action and the former inhibiting it [105][106][107][108][109], the PPXinduced decrease in the mRNA levels of both C-fos and Zif268 in the NAc Core associated with sustained C-fos expression in the Shell of HI rats suggests a PPX-induced ventral striatum-mediated normalization of impulse control at a time HI rats have re-engaged their goal-directed system. While the present results highlight the role of the NAc Core in the modulatory effects pf PPX on impulsivity, other studies have also previously demonstrated using a similar 5-CSRTT paradigm that the NAc Shell [107,108], and its innervation by the VTA [110,111] also contribute to the control of impulsivity.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, considering the functional antagonism in the control over waiting impulsivity between the NAc Shell and the NAc Core, the latter promoting impulsive action and the former inhibiting it [105][106][107][108][109], the PPXinduced decrease in the mRNA levels of both C-fos and Zif268 in the NAc Core associated with sustained C-fos expression in the Shell of HI rats suggests a PPX-induced ventral striatum-mediated normalization of impulse control at a time HI rats have re-engaged their goal-directed system. While the present results highlight the role of the NAc Core in the modulatory effects pf PPX on impulsivity, other studies have also previously demonstrated using a similar 5-CSRTT paradigm that the NAc Shell [107,108], and its innervation by the VTA [110,111] also contribute to the control of impulsivity.…”
Section: Discussionsupporting
confidence: 66%